The Impact of Export Processing Zones on Employment, Wages and Labour Conditions in Developing Countries : Systematic Review - Cirera, Xavier; Lakshman, Rajith W.D. (Taylor and Francis, 2017)
One of the most common instruments of industrial policy is Export Processing Zones (EPZs). This paper shows the results of a systematic review of the impact of EPZs on employment, wages and labour conditions in developing countries. The results of synthesising 59 studies suggest that there is no robust evidence that the employment created in the zones is additional. Also, in most cases, EPZs pay higher wages and do not contribute to increase the gender wage gap. The results regarding labour conditions such as health and safety, unionisation or hours worked are mixed when comparing with firms outside the EPZ.